Inclusive tourism development in Sortavala district of the Republic of Karelia - Plotnikova, V. S.; Afonina, O. D.; Maximov, M. I. (Russian State University of Tourism and Service (RSUTS), 2023)
The problem of availability of tourism infrastructure for disabled tourists is being discussed by the tourism community and is of great social importance. This type of tourism involves access without any restrictions for all people to tourist services and products. It is provided by accessible environment: visual, auditory, cognitive, mobile. The article deals with organizational issues related to the provision of tourist services to disabled people. The criteria of an accessible environment should consider the convenience, safety, comfort and informativeness of routes for disabled people. The authors analyze the accessibility of the area and tourist infrastructure in the Sortavala district of the Republic of Karelia, as well as transport accessibility, availability of accommodation facilities, food, tourist facilities, leisure facilities located in the area. Based on this analysis, the article presents recommendations for the inclusive tourism development in the region and a draft model of an informational barrier-free site, accumulating information about tourism products and tourism infrastructure and aimed at developing accessible tourism for citizens with disabilities. The implementation of the Accessible Tourism portal will make it possible to bring information about special programs for disabled people, adapted both in terms of accessibility and cost to target groups, to form stable associations of people with limited mobility for organized recreation. These measures will assist in introducing tourists with special needs to cultural and educational tourism and the realization of their right to rest.